Gender, civic engagement, and the importance of integrating spirituality - Miles, Jeffrey A. (Journal of beliefs and values, 2023)
Spirituality is associated with a variety of positive life outcomes, and the university experience has long been regarded as a critical period of spiritual identity development. A key explanation for why gender differences exist in the importance of integrating spirituality in one’s life may be that civic engagement is intervening in the relationship. We administered surveys to 964 first-year undergraduate students in the western United States. Women had higher scores for civic engagement and the importance of integrating spirituality into their lives than men. Civic engagement mediated the influence of gender on the importance of integrating spirituality into one’s life. Implications are discussed.